Memaknai Aktifitas Belajar Sebagai Ibadah Dengan Kontekstualisasi Pemahaman Hadist Innamal A’malu Bin Niyat - Ahmad Hanafi (Lembaga Penerbitan dan Publikasi Ilmiah IAI Bunga Bangsa Cirebon, 2020)
Learning or studying is an activity that must be carried out throughout the ages. Do not recognize age or gender. Does not recognize distance or geographical conditions. Since the primordial vows in the form of testimony to one divinity and Muhammad's prophethood were made, this obligation has been attached to him. However, this study does not intend to further explore the chapter on studying knowledge, the notes of which are well coded and neatly arranged in the classical books on hadith. Furthermore, the author would like to try to elaborate a hadith text which is neither textually nor contextually related to learning or studying problems. Namely the hadiths about everything depends on the intention. Looking at the asbabul wurud hadith, the context is related to the issue of hijrah. Namely, during the migration from Mecca to Medina, there were various intentions among the friends who had emigrated. Some are because of wealth, some are because of women, there are also those who are Lillahi ta'ala. A hadith, as well as the words of other great figures of the world, is always understood by various interpretations. Moreover, the great figure in question has long since died. Plus, the distance or time of his life is very far apart from the interpreter. Many years. Hundreds or even thousands of years. Of course what emerges is that there are various interpretations and understandings. Some are